Coordinated neural, behavioral, and phenomenological changes in perceptual plasticity through overtraining of synesthetic associations. (March 2018) - Rothen, Nicolas; Schwartzman, David J.; Bor, Daniel; Seth, Anil K.
Abstract: Synesthesia is associated with additional perceptual experiences, which are automatically and consistently triggered by specific inducing stimuli. Synesthesia is also accompanied by more general sensory and cortical changes, including enhanced modality-specific cortical excitability. Extensive cognitive training has been shown to generate synesthesia-like phenomenology but whether these experiences are accompanied by neurophysiological changes characteristic of synesthesia remains unknown. Addressing this question provides a unique opportunity to elucidate the neural basis of perceptual plasticity relevant to conscious experiences. Here we investigate whether extensive training of letter-color associations leads not only to synesthetic experiences, but also to changes in cortical excitability. We confirm that overtraining synesthetic associations results in synesthetic phenomenology. Stroop tasks further reveal synesthesia-like performance following training. Electroencephalography and transcranial magnetic stimulation show, respectively, enhanced visual evoked potentials (in response to untrained patterns) and lower phosphene thresholds, demonstrating specific cortical changes. An active (using letter-symbol training) and a passive control confirmed these results were due to letter-color training and not simply to repeated testing. Summarizing, we demonstrate specific cortical changes, following training-induced acquisition of synesthetic phenomenology that are characteristic of genuine synesthesia. Collectively, our data reveal dramatic plasticity in human visual perception, expressed through a coordinated set of behavioral, neurophysiological, and phenomenological changes. Highlights: Prolonged synesthetic associations training results in synesthetic phenomenology. Trained synesthetic phenomenology is associated with perceptual differences in visual areas. Trained synesthetic phenomenology is associated with behavioral synesthetic markers. Prolonged association training does not generally lead to similar cortical changes. Collectively, the data reveal dramatic plasticity in human visual perception.